Should we provide outreach rehabilitation to very old people living in Nursing Care Facilities after a hip fracture? A randomised controlled trial. (22nd February 2019) - Crotty, Maria; Killington, Maggie; Liu, Enwu; Cameron, Ian D; Kurrle, Susan; Kaambwa, Billingsley; Davies, Owen; Miller, Michelle; Chehade, Mellick; Ratcliffe, Julie
Abstract: Objective: to determine whether a 4-week postoperative rehabilitation program delivered in Nursing Care Facilities (NCFs) would improve quality of life and mobility compared with receiving usual care. Design: parallel randomised controlled trial with integrated health economic study. Setting: NCFs, in Adelaide South Australia. Subjects: people aged 70 years and older who were recovering from hip fracture surgery and were walking prior to hip fracture. Measurements: primary outcomes: mobility (Nursing Home Life-Space Diameter (NHLSD)) and quality of life (DEMQOL) at 4 weeks and 12 months. Results: participants were randomised to treatment ( n = 121) or control ( n = 119) groups. At 4 weeks, the treatment group had better mobility (NHLSD mean difference −1.9; 95% CI: −3.3, −0.57; P = 0.0055) and were more likely to be alive (log rank test P = 0.048) but there were no differences in quality of life. At 12 months, the treatment group had better quality of life (DEMQOL sum score mean difference = −7.4; 95% CI: −12.5 to −2.3; P = 0.0051), but there were no other differences between treatment and control groups. Quality adjusted life years (QALYs) gained over 12 months were 0.0063 higher per participant (95% CI: −0.0547 to 0.0686). The resulting incremental cost effectiveness ratios (ICERs) were $5, 545 Australian dollars per unit increase in the NHLSD (95% CI: $244 to $15, 159) and $328, 685 per QALY gained (95% CI: $82, 654 to $75, 007, 056). Conclusions: the benefits did not persist once the rehabilitation program ended but quality of life at 12 months in survivors was slightly higher. The case for funding outreach home rehabilitation in NCFs is weak from a traditional health economic perspective. Trial registration: ACTRN12612000112864 registered on the Australian and New Zealand Clinical Trials Registry. Trial protocol available at https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id = 361980